Contextual predictive factors of child sexual abuse: The role of parent-child interaction (2011)
Objectives: To determine the prevalence of child sexual abuse in the Colombian coasts, as well as to assess the role of parent-child interactions on its occurrence and to identify factors from different environmental levels that predict it. Methods: This cross-sectional study explores the results of 1,089 household interviews responded by mothers. Descriptive analyses and multivariate logistic regressions were conducted, with child sexual abuse regressed on parent-child interactions, children's characteristics, maternal characteristics, family characteristics, and community characteristics. Results: 1.2% of the mothers reported that their children had been sexually abused. Families that communicated with their children were less likely to report child sexual abuse, each additional standard deviation of communication reduced child sexual abuse 3.5 times. Affection and negative treatment to the children were not associated with child sexual abuse. Families who experienced intimate partner violence and violent communities were more likely to experience child sexual abuse. Conclusions: Interventions are needed to address the problem of child sexual abuse. © 2011 Elsevier Ltd.